BODY IMAGE AS THE BASIS FOR POSITIVE SOCIALIZATION OF YOUNG CHILDREN - Lykova, Irina; Kozhevnikova, Victoria (Revista Inclusiones, 2020)
The authors raise an understudied problem of the development of body image as a “sign” of personality development and one of the mechanisms of successful socialization of an individual in early childhood. Based on the terminological analysis, the concept of “positive socialization of young children” is specified and the concept of “body image” is unfolded in a sociocultural context. The materials and results of an experimental study of the dependence of “body image” interpretations on parenting styles are provided. The potential of various forms of art for improving teachers’ and parents’ awareness of the significance of “body image” for positive socialization of young children is identified.